Formación ocupacional del personal y control de calidad en las panaderías de Huamachuco, año 2016 - Rondo Layza, Francisca (2017)
This thesis has taken place in the bakeries of the city of Huamachuco, Province of Sánchez Carrión, Region of La Libertad, Peru; Its main objective is "to sustain how the Occupational Training of personnel influences the Quality Control of the bakeries of Huamachuco, year 2016". The problem of silver research indicates: In what way does the Occupational Training of staff influences the Quality Control of the bakeries of Huamachuco, year 2016?. For data collection, three populations have been taken into account: 30 representatives of neighborhood councils (3 per zone), 30 workers (3 per bakery) and 3 municipal inspectors; for being small "sample = population"; to which the respective survey was applied. According to the results obtained, and following the scientific method has been carried out the corresponding analysis and discussion, coming to demonstrate the validity of the hypothesis that establishes that: "The Occupational Training of the personnel directly and significantly influences the Quality Control of the Bakeries of Huamachuco, year 2016". As a final part the conclusions and recommendations have been formulated, the main conclusion establishes that the Occupational Training of the personnel as the Quality Control of the bakeries of Huamachuco qualifies at "average" level, showing a prominent position the bakery Campos y Rico Pan, And a position relegated the Carmencita bakery, and the main recommendation states that bakeries that present an unfavorable position regarding the Occupational Training of their workers, should be more demanding in the admission process and take advantage of the training offered free of charge in the City of Huamachuco; In addition they must be careful in the quality control of their products, processes and facilities.